Lightlike Submanifolds of a Semi-Riemannian Manifold of Quasi-Constant Curvature - D. H. Jin; J. W. Lee (Journal of Applied Mathematics)
We study the geometry of lightlike submanifolds (𝑀,𝑔,𝑆(𝑇𝑀),𝑆(𝑇𝑀⟂)) of a semi-Riemannian manifold (𝑀,̃𝑔) of quasiconstant curvature subject to the following conditions: (1) the curvature vector field ζ of 𝑀 is tangent to 𝑀, (2) the screen distribution 𝑆(𝑇𝑀) of 𝑀 is totally geodesic in 𝑀, and (3) the coscreen distribution 𝑆(𝑇𝑀⟂) of 𝑀 is a conformal Killing distribution.